Legal Perspectives on Breast Grabbing as an Act of Sexual Harassment: Comparing Indonesian Positive Law with Islamic Criminal Law: Perspektif Hukum tentang Begal Payudara sebagai Tindakan Pelecehan Seksual: Membandingkan Hukum Positif Indonesia dengan Hukum Pidana Islam - Fahmi, Zul; Fakhyadi, Defel; Pebriyanti; Asrofi; Suroto (Al-Jinayah : Jurnal Hukum Pidana Islam, 2025)
This research examines the phenomenon of breast grabbing as an act of sexual harassment that threatens the dignity and well-being of the victim, as well as exposing shortcomings in the legal protection system in Indonesia. This research aims to compare the handling of breast begging/grabbing cases according to Indonesian positive law and Islamic criminal law, analyze the social impacts caused, and explore more effective prevention strategies. This research employed a qualitative method and a normative approach, incorporating a literature review. The results show that Indonesian positive law provides broader protection for the psychological impact of victims and imposes strict sanctions, including imprisonment, for perpetrators. In contrast, Islamic criminal law emphasizes moral recovery and social balance, as well as sanctions determined based on the concept of ta’zīr, which considers the benefit to society. The synergy between the two legal systems is a strategic step in formulating more effective prevention and law enforcement policies for breast grabbing, and opens up opportunities for further research to develop a legal framework that is responsive to social dynamics and the values of justice.